The coupling of the hydrated proton to its first solvation shell - Markus Schröder; Fabien Gatti; David Lauvergnat; Hans-Dieter Meyer; Oriol Vendrell (Nature Communications, 2022)
The Zundel [H(H2O)2]+ and Eigen [H(H2O)4]+ cations exhibit radicallly different infrared spectra and are the limiting dynamical structures involved in proton mobility in liquid water. Here, the authors find through quantum dynamics simulations that two polarized water molecules and a proton suffice to explain the key spectroscopic features connected to proton mobility for both species.